Health condition of ageing populations of the European Union - Sojka Elżbieta (Bulletin of Geography. Socio-Economic Series)
The paper is a comparative analysis of health condition of EU-27 states that are differentiated with respect to demographic situation and the level of social and economic development with the use of methods of multidimensional comparative analysis. Relationships between macroeconomic values and health indices of EU populations were also studied with the use of demometric models. The study was performed for 2009. The most favourable health situation (in the light of diagnostic qualities adopted for the study) was observed in Cyprus, where the value of synthetic measure was almost 0.9. Cyprus is a relatively young country, with the lowest rate of mortality due to malicious tumours among all the countries of the European Community. Apart from Cyprus, Ireland was found in the first group (the lowest rate of people at 65+ years of age of all EU countries), Luxembourg (low rate of infant mortality) and Spain (relatively low mortality due to diseases of circulatory system). Definitely the worst health situation was observed in majority of the countries of the former Eastern bloc. On the grounds of the correlation diagram it was possible to conclude that, together with social and economic development of the country and resulting growth in expenditures on health protection per capita, mean life expectancy at birth significantly extended. However, these relations are not linear. Logarithmically constructed regression functions proved a strong and statistically significant impact of macroeconomic values on indices of population health condition.